Participated observation of nursing child health consultation - Loureiro, Fernanda Manuela; Silva, José António Neto Ferreira da; Quitério, Margarida Maria de Sousa Lourenço; Charepe, Zaida Borges (Revista da Escola de Enfermagem da USP, 2012)
Situation diagnosis using exploratory and descriptive scientific methodology (participant observation with descriptive statistical treatment) in order to identify nursing' practices in the area of health promotion during a nursing child health consultation. The 31 consultations observed (n = 31) showed that the majority of observations occurred in children younger than 2 years being the most discussed topic feed with predominant use of expository methodology. There was also little use of informational support and when used relate to the themes of security and nutrition. Most providers raised questions and there was limited registration of the interaction between provider and child with an expenditure averaging of 23 minutes per consultation. Given the results and reflecting about them stands out as intervention the construction of a health promotion manual with the integration of theory and evidence of good practice in this area.